Carbon dioxide capture from biomass pyrolysis gas as an enabling step of biogenic carbon nanotube synthesis and hydrogen recovery - Veksha, Andrei (2023)
Utilization of renewable raw materials as feedstock defossilizes industrial manufacturing while subsequent carbon capture reduces carbon footprint. We applied this concept to design a new pyrolysis-based process for synthesis of biogenic multi-walled carbon nanotubes (MWCNTs) and H2 from biomass. It was demonstrated that the conversion of hydrocarbon compounds in pyrolysis gas into MWCNTs and H2 is detrimentally influenced by accompanied CO2 released from biomass decomposition. Capturing CO2 with a calcium sorbent upgraded the pyrolysis gas into a suitable gaseous precursor for downstream production of MWCNTs and H2 -rich gas. Furthermore, the results suggest that CO2 capture with the sorbent has a potential to outperform a liquid alkaline scrubber owing to avoided liquid organic waste generation, sorbent regenerability and higher H2 recovery from biomass pyrolysis gas.